PERAN SIG DALAM PENERAPAN SMART CITY DI INDONESIA - Herika Taki (Jurnal Lingkungan dan Kota, 2022)
GIS is developing rapidly in responding to the challenges of the times related to spatial or spatial solutions, in Indonesia itself the development of GIS is very fast, especially in life applications and one of the benefits of GIS is in the application of smart cities where technological advances are combined with spatial analysis, but in its development, there are still deficiencies in the application of GIS in this smart city include limited funds, technology updates, and others. For this reason, this article examines the application of GIS in smart cities in Indonesia along with examples of its application and to what extent this implementation can be carried out successfully, and how much benefit can be obtained related to time effectiveness and cost efficiency. The research method used in this paper is a qualitative approach by multiplying secondary data collection based on reference sources from books, journals, and other scientific publications and supported by digital information sources such as websites. The data analysis method used is to study GIS and smart city in theory and then display examples of its application to cities in Indonesia so that the result is that the smart city concept through this sig has succeeded in helping the city improve its general service quality and increase the moderation of the city as a whole technology. The conclusion from this study is that the role of GIS is very large in assisting the application of sig, especially in providing spatial data and making decisions based on spatially analyzed spatial data by combining various binding factors.